Stereotactic surgery through beta-amyloid1-42 : a valid experimental model for cognitive changes in rodents - Moura, Felipe Carmo de (2016)
Neurodegenerative diseases are a progressive neurological disorders class with signs and symptoms caused by Central Nervous System (CNS) deterioration cells. Alzheimer’s disease (AD) is pathology without accurate knowledge of its etiology and beta - amyloid peptide (Aβ) presence in CNS is the main structural feature. Memory and learning cognitive loss are associated with AD and appear as disease first signs. Thus researches aimed at new the rapeutic approaches are primarily applied in animal models and require a similar model for their treatments. Several models are presented, but through a thorough literature search, we found model induced by stereotaxic surgery with Aβ injection presents a viable way to reproduce cognitive losses in a short time period. Through Morris Water Maze behavioral test, it is possible verify such losses related to memory and learning after seven days from surgery. It is therefore concluded that Aβ 1 - 42 injections in stereotaxic surgery are a valid experimental model to induce changes similar to AD.